(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The quality of healthcare providers depends on the extent to which the provider's services increase the chance of getting the desired health outcome. Researchers have provided different approaches to measuring the quality of hospital services. Hospitals can provide different services, including clinical and non-clinical ones. Patients' perception of hospital functions is a valuable alternative tool to measure the quality of hospital services. Hence, the study has evaluated the service quality of private hospitals in district Kamrup (metro), Assam. MethodThe sample size is determined by using a purposive random sampling technique. The five dimensions of the SERVQUAL model are used. Further, a paired t-test is conducted to examine the significance of the gap between perception and expectation. ResultsThe model is statistically fit to explain the objective of the study. All the dimensions have shown a negative gap and are statistically significant. The highest average gap is observed in the empathy dimension, while the minimum average gap is observed in the responsibility dimension.ConclusionThe study will help the management of the concerned hospitals to improve their functional quality. The sample size is determined randomly, through which expectations and experiences of sample units are reflected only. However, socio-demographic factors can also affect the result of the study, which is not considered. Hence there is a scope for deeper investigation.